STRUCTURE OF THE HYDROTHERMAL ROOT ZONE OF THE SHEETED DIKES IN FAST-SPREAD OCEANIC CRUST: A CORE-LOG INTEGRATION STUDY OF ODP HOLE 1256D, EASTERN EQUATORIAL PACIFIC - Violay*, Marie; Pezard, Philippe A.; Ildefonse, Benoit; Célérier, Bernard; Deleau, Agathe (Ofioliti, 2012)
Ocean Drilling Program Hole 1256D reached for the first time the transition zone between the sheeted dike complex and the uppermost gabbros. The recovered crustal section offers a unique opportunity to study the deepest part of the hydrothermal system in present-day oceanic crust. We present a structural analysis of electrical borehole wall images. We identified, and measured the orientations of four categories of structures: major faults, minor fractures, possibly hydrothermal veins, and dikes. All structures tend to strike parallel to the paleo-ridge axis. Three major fault zones (meter thick) and dikes are steeply dipping (~ 75° on average) outward the ridge. Centimeter-thick moderately conductive planar features are interpreted as hydrothermal veins, are organized in arrays of consistent spacing, thickness, and orientation, and are dipping about 15-20° toward the ridge. This structural pattern is interpreted as an on-axis paleohydrothermal circulation system, with vertical, dike-parallel fractures, and sub-horizontal high-temperature hydrothermal veins at the base of the sheeted dike, which was subsequently rotated ~ 15° westward around a ridge-parallel, sub-horizontal axis. This rotation can be caused by upper-crustal block rotation along a listric normal fault, and/or subsidence at the ridge axis.